Clinical relevance of cone beam computed tomography in mandibular third molar removal: A multicentre, randomised, controlled trial. Issue 10 (December 2015) - Ghaeminia, H.; Gerlach, N.L.; Hoppenreijs, Th.J.M.; Kicken, M.; Dings, J.P.; Borstlap, W.A.; de Haan, T.; Bergé, S.J.; Meijer, G.J.; Maal, T.J.
Abstract: Purpose: The aims of this study were to investigate the effectiveness of cone beam computed tomography (CBCT) compared to panoramic radiography (PR), prior to mandibular third molar removal, in reducing patient morbidity, and to identify risk factors associated with inferior alveolar nerve (IAN) injury. Material and methods: This multicentre, randomised, controlled trial was performed at three centres in the Netherlands. Adults with an increased risk for IAN injury, as diagnosed from PR, were included in the study. In one arm of the study, patients underwent an additional CBCT prior to third molar surgery. In a second arm of the study, no additional radiographs were acquired. The primary outcome measure was the number of patient-reported altered sensations 1 week after surgery. As secondary outcome measures, the number of patients with objective IAN injury, with long-term (>6 months) IAN injury, the occurrence of other postoperative complications, the Oral Health Related Quality of Life–14 (OHIP-14) questionnaire responses, postoperative pain (visual analogue scale score), duration of surgery, number of emergency visits, and number of missed days of work or study were scored. Results: A total of 268 patients with 320 mandibular third molars were analysed according to the intention-to-treat principle. The overall incidence of IAN injury 1 week after surgery was 6.3%. No significant differences between CBCT and PR for temporary IAN injury ( p = 0.64) and all other secondary outcomes were registered. A lingual position of the mandibular canal (MC) and narrowing, in which the diameter of the MC lumen was decreased at the contact area between the MC and the roots, were significant risk factors for temporary IAN injury. Conclusion: Although CBCT is a valuable diagnostic adjunct for identification of an increased risk for IAN injury, the use of CBCT does not translate into a reduction of IAN injury and other postoperative complications, after removal of the complete mandibular third molar. In these selected cases of a high risk for IAN injury, an alternative strategy, such as monitoring or a coronectomy, might be more appropriate. (http://clinicaltrials.gov, NCT02071030 ).